2012
DOI: 10.1038/nature11244
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell potency fluctuates with endogenous retrovirus activity

Abstract: Summary Embryonic stem (ES) cells are derived from blastocyst stage embryos and are believed to be functionally equivalent to the inner cell mass, which lacks the ability to produce all extraembryonic tissues. Here we report the identification of a rare transient cell population within mouse ES and induced pluripotent stem (iPS) cell cultures that express high levels of transcripts found in two-cell (2C) embryos in which the blastomeres are totipotent. We genetically tagged these 2C-like ES cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

99
1,542
4
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 982 publications
(1,652 citation statements)
references
References 43 publications
(45 reference statements)
99
1,542
4
7
Order By: Relevance
“…The expression of Zscan4 was also correlated with increased contribution to the embryo in tetraploid aggregations. A similar population expressing Zscan4 was identified based on the expression of murine endogenous retrovirus with leucine tRNA primer (MuERV-L) elements [31]. Mouse embryos at the 2C stage express a number of MuERV-L retroviral elements and these elements drive the expression of more than 100 2C-specific genes.…”
Section: Totipotent Cellsmentioning
confidence: 99%
“…The expression of Zscan4 was also correlated with increased contribution to the embryo in tetraploid aggregations. A similar population expressing Zscan4 was identified based on the expression of murine endogenous retrovirus with leucine tRNA primer (MuERV-L) elements [31]. Mouse embryos at the 2C stage express a number of MuERV-L retroviral elements and these elements drive the expression of more than 100 2C-specific genes.…”
Section: Totipotent Cellsmentioning
confidence: 99%
“…For example, since human ESCs bear numerous similarities to EpiSCs [5,6], our model predicts that ectopic Cdx2 would not induce expression of TSC-like cell genes in human ESCs in the conditions we tested here. Recently, totipotent or naïve pluripotent stem cell lines have been derived from both humans and mice [56][57][58][59][60]. In several cases, these cell lines have been shown to contribute to extraembryonic lineages in chimeras.…”
Section: Figmentioning
confidence: 99%
“…An RNA-seq comparison between miR-34a -/-and WT induced pluripotent stem cells (iPSCs) confirmed the correlation between bi-potential ESCs and MERVL activation [3,4], where MERVL family transcripts were among the most highly and differentially expressed in miR-34a -/-iPSCs. Probing the expression of the MERVL-gag protein showed that miR-34a -/-pluripotent cultures are heterogeneous in relation to MERVL activation.…”
mentioning
confidence: 93%
“…By using a reporter vector under the regulation of a MERVL element, it has been shown that within cultured ESC populations, 2C-like/bi-potential cells spontaneously arise at very low percentages [3]. These bi-potential cells resemble totipotent 2C-stage embryos in several key features: (i) activation of MERVL loci and MERVL-proximal genes, (ii) lack of core pluripotency protein expression (Oct4/Sox2/Nanog), (iii) an extended (or bi-potential) cellfate potential allowing contribution to both embryonic and extraembryonic lineages.…”
mentioning
confidence: 99%
See 1 more Smart Citation